دراسة إستشرافية لفتح الشبابيك الإسلامية بالبنوك التجارية دراسة حالة الجزائر (البنك الوطني الجزائري _ وكالة ولاية بشار) . - بلعابد, فايزة; لمطوش, لطيفة (جامعة الوادي - University of Eloued, 2023)
الهدف من الدراسة تسليط الضوء على تجربة فتح الشبابيك الإسلامية بالبنوك التجارية الجزائرية من حيث إعتمادها لأحكام و مبادئ الشريعة الإسلامية من جهة، و التنبؤ بنتائج هذه التجربة المفتعلة على مستوى البنوك التجارية و بالتالي إنعكاساتها على الإقتصاد الوطني من جهة أخرى، و على هذا اساس تم الأخذ بالمنهج الوصفي للإلمام بالإطار المفاهيمي لكل من البنوك التجارية و الشبابيك الإسلامية مع الإشارة إلى أهم شروط اعتمادها بالجزائر، والمنهج التحليلي القائم على تقييم و تحليل إجابات أسئلة المقابلة و التي اعتمادها كأداة في دراسة الحالة على مستوى وكالة النبك الوطني الجزائري (بولاية بشار). من خلال الإجابات المتوصل إليها يمكن التنبؤ بنجاح هذه التجربة كما يمكن أن تصبح رائدة على المستوى المحلي والوطني معا، لكن شريطة أن تسعى الدولة جاهدة إلى التخفيف من حدة العوائق التي في طريق هذه الشبابيك، والى إعتماد اهم مقومات نجاح هذه التجربة الداخيلة من تدريب للموظفين والتثقيف الشرعي لهم على مستوى البنوك التجارية بالدرجة الأولى و الإجتهاد لأجل تحقيق رقابة شرعية محظى بكل معاملاتها مع زبائنها . The aim of the study is to shed light on the experience of opening Islamic windows in Algerian commercial banks in terms of its adoption of the provisions and principles of Islamic law on the one hand, and to predict the results of this fabricated experiment at the level of commercial banks and, consequently, its repercussions on the national economy on the other hand, On this basis, the descriptive approach was taken to get acquainted with the conceptual framework for each of the commercial banks and Islamic windows, with reference to the most important conditions for their adoption in Algeria, and the analytical approach based on the evaluation and analysis of the answers to the interviewquestions, which was adopted as a tool in the case study at the level of the Algerian National Bank Agency ( in the province of Bashar), Through the answers reached, it is possible to predict the success of this experiment, as it can become a pioneer at the local and national levels together, but provided that the state strives to mitigate the obstacles in the way of these windows, and to adopt the most important ingredients for the success of this internal experience, such as training for employees and education.Shari’a for them at the level of commercial banks in the first place and diligence in order to achieve legitimate control that enjoys all its dealings with its customers.
A prospective study to open Islamic windows in commercial banks Algeria case study (Algerian National Bank _ Bechar Province Agency)
مقال
Keywords: شبابيك إسلامية، بنوك تقليدية، بنك وطني جزائري، وكالة بشار ، مرابحة، إجازة، ضوابط.; Islamic windows; traditional banks; Algerian National Bank; Bashar agency; Murabaha; license; controls